ANALISIS HUBUNGAN MINAT DAN MOTIVASI DENGAN KECEMASAN SISWA SD PADA KEGIATAN MARKET DAY - Mega Isvandiana Purnamasari dan Erna Setyowati (Universitas PGRI Yogyakarta, 2019)
AbstractFactors in students, some of which are anxiety, motivation and interest. These are the studentsâ€™ internal factors that influence each of their activities in school, one of which is â€œMarket Dayâ€ activities. This study aims to determine the relationship between motivation and interest both singly and in combination with students' anxiety in participating in â€œMarket Dayâ€ activities. This study uses causal correlation techniques with motivatio (x1) and interest (x2) as free variables and the bounded variables namely anxiety (y). Data was taken using a questionnaire with a Likert scale. The data was taken from two elementary schools in Pacitan with the amount of respondents as many as 116 students from grades 4, 5 and 6. The data analysis was carried out using simple and multiple linear regression analysis methods. The results of data analysis concluded that: 1) Motivation is not related to students' anxiety in participating in â€œMarket Dayâ€ activities. 2) Interest has a negative relationship with students' anxiety in participating in â€œMarket Dayâ€ activities. The negative relationship was at the strong level with an effective contribution of 62.1%. And 3) Motivation and interest jointly have a strong relationship with students' anxiety in participating in â€œMarket Dayâ€ activities. The relationship has an effective contribution of 63.3%, where 2% comes from motivational factors and 61.3% comes from interest factors.Keywords:Motivation, Anxiety, Interest, Market Day